Identifying trades tutors' and institutions' perceptions of tutors' roles within the ITP sector : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Adult Education at Massey University, Palmerston North, New Zealand - Pritchard, Christine (Massey University, 2008)
Since 1984 tertiary education institutions have been subject to progressive and far-reaching change. Much of this change has been shaped by neo-liberalist agendas which espouse accountability, efficiency, responsiveness, professionalism and managerialism. This thesis looks at how these themes have shaped or influenced managerial and tutorial perceptions of tutors' operational roles, responsibilities and performance within a selection of contemporary Institutes of Technology and Polytechnics (ITP) teaching environments. Analysis of the research identifies that scant or poorly prepared institutional documentation around tutorial roles and responsibilities has contributed to uncertainty or confusion, and consequently to individuals adapting their teaching roles to suit themselves. It has also been identified that managers appointed to the pivotal role of Head of School are stretched in their ability to cope with the demands that are placed on them. This thesis suggests that the increasing responsibilities they carry for managing tutorial staff have contributed to a breakdown in workload planning and performance management processes. Managers acknowledge that further work needs to be done in defining tutors' roles, responsibilities and performance. But such work presupposes the question: how do managers and tutors perceive tutorial roles in today's ITP teaching environment? Research on this key question and associated issues provides the basis for this thesis.
Keywords: Technical education teachers; Teacher effectiveness; Educational change; Technical institutes; Administration; New Zealand; Attitudes; Evaluation